Seamless Learning Model; Teachers' Perception of Learning Adaptation in Madrasah - Fathor Rozi; Nur Fitriya (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
The transition to learning, which was initially in the classroom and then at home, requires many parties to use technology as an online (online) learning medium. This displays the true concept of learning that must be adaptive to any situation.This study aimed to examine in-depth and determines the perceptions of madrasah ibtidaiyah teachers to the seamless learning model at Madrasah Ibtiddaiyah Islamiyah in Rondokuning Village, Kraksaan. This research uses a qualitative approach with the type of case study. Data collection techniques used by researchers are observation and in-depth interviews. While the data analysis techniques used are data reduction, data presentation, and conclusion of research results. The research results show that the seamless learning model raises five general perceptions in the teacher paradigm as the impact of limited facilities and infrastructure. The implication of the teacher's perception of the Seamless Learning model makes it easier for students and teachers to implement Learning in schools.